Petrogenesis of Andesite Rocks in Datae Area, Sidenreng Rappang Regency, South Sulawesi Province - Sayidatina Hayatuzzahra; Septyo Uji Pratomo (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
The research area is in the Datae Area, Watangpulu District, Sidenreng Rappang Regency, South Sulawesi Province. This study aims to determine the distribution of volcanic rocks, determine the crystallization phase based on petrographic analysis, and determine the type, magma affinity and tectonic environment based on geochemical data. The method used in this study was field data collection and rock sampling for analysis through petrographic analysis and geochemical analysis using the X-Ray Fluorescence (XRF) method by analysing the main elements, trace elements and rare earth elements (REE). The results of the petrographic analysis show that the rocks found in the field are volcanic breccia and ignimbrite. Volcanic breccia showed coarse-grained texture composed of angular to rounded andesite fragments and pyroclastic material fused together in a matrix. Meanwhile, ignimbrite showed fine grained texture with lapilli to boulder-sized fragments, poor sorting, open-packed and non-layered structure. Based on the Total Alkali Silika (TAS) diagram, AFM diagram, and binary diagram, the results of the geochemical analysis showed that the rocks found in the study area were andesite and trachy-andesite, while the magma affinity area is high-K calc-alkaline and shoshonitic. High-K calc-alkaline magmas are associated with subduction zones and are characterized by elevated levels of potassium and aluminum, while shoshonitic magmas are typically found in intraplate or back-arc settings, characterized by their distinctive potassium, sodium, and barium-rich compositions. The results from ternary diagram and geochemical Spider plots proved that the magma tectonic environment is island arc—continental arc basalt, indicating that the rock was formed in a subduction area. This research supports previous research regarding the tectonics of the western arm of Sulawesi, which stated that this area was formed by subduction.